Pe cine "alegem" online? Criterii ale alegerii partenerului de cuplu în spaţiul virtual - Raluca Buhaş (Sociologie Românească, 2014)
Although skeptics do not completely accept cyberspace as a modern but natural frame for establishing and maintaining diverse relationships, in the last few years the online environment has become a common and useful social context for those who have embraced the digital reality in their everyday life. If we rely on web sites to search information and data, pay our bills on the Internet, go for an online shopping session, why shouldn`t we search our soul-mate online? The fact that more and more individuals choose to access the Internet in order to ﬁnd “that special person”, assigns the online environment as a popular way to interconnect with others. Being a relatively new subject of scientiﬁc interest on the Romanian sociological stage, the present investigation has an explorative and descriptive speciﬁc. The sociological investigation addressed in the present paper was conducted by applying an online questionnaire to individuals who form a couple with partners they have met in cyberspace. We explore and discuss the socio-demographic and cultural criteria that are standing on the basis of partner selection process in cyberspace. In the end, a synthetized model regarding these socio-demographic determinants is generated. Social homogamy, spatial proximity and physical attractiveness are outlined as the most important criteria in the online process of partner selection.